Improved survival after orthotopic liver grafting. Issue 6284 (11th July 1981) - Calne, R Y; Williams, R; Lindop, M; Farman, J V; Tolley, M E; Rolles, K; MacDougall, B; Neuberger, J; Wyke, R J; Raftery, A T; Duffy, T J; Wight, D G; et al.
Abstract : A total of 108 orthotopic liver transplants have been carried out in the Cambridge/King's College Hospital series. Over 13 years, changes in patient selection, immunosuppression, and surgical and anaesthetic techniques have led to a steady improvement in results. Results obtained in the last 22 patients indicated that over half survive for one year. Although at considerable risk during the operation, patients with non-malignant cirrhotic diseases who survive one year have a good long-term chance of survival